2015
DOI: 10.1007/s13353-015-0325-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci with sex-specific effects for internal organs weights and hematocrit value in a broiler-layer cross

Abstract: Rapid growth in broilers is associated with susceptibility to metabolic disorders such as pulmonary hypertension syndrome (ascites) and sudden death. This study describes a genome search for QTL associated with relative weight of cardio respiratory and metabolically important organs (heart, lungs, liver and gizzard), and hematocrit value in a Brazilian broiler-layer cross. QTL with similar or different effects across sexes were investigated. At 42 days of age after fasted for 6 h, the F2 chickens were weighed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…We performed the GWAS studies in a F2 experimental population generated from a cross between a white-egg type (layer, CC) line and a meat-type (broiler, TT) line 30 . These lines have a different background and previously underwent multi-trait selection for different traits for several generations, exhibiting considerable differences in growth and carcass traits 8 , 31 . According to Campos et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the GWAS studies in a F2 experimental population generated from a cross between a white-egg type (layer, CC) line and a meat-type (broiler, TT) line 30 . These lines have a different background and previously underwent multi-trait selection for different traits for several generations, exhibiting considerable differences in growth and carcass traits 8 , 31 . According to Campos et al .…”
Section: Discussionmentioning
confidence: 99%
“…This F 2 -TCTC generation was previously used to map numerous QTLs for performance, carcass and chemical component traits 8 10 , 31 , 33 , 75 using microsatellite markers. For the study reported in this paper, selection of families for genotyping and GWAS was based on F1 males that appeared to be heterozygous for QTL effects reported in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, QTLs have been mapped for various carcassrelated traits, including carcass weight, muscle weight, bone weight, viscera weight, and its ratio to carcass weight or body weight at slaughtering age (Sharman et al, 2007;Ankrabadu et al, 2010b;Nassar et al, 2012;Moura et al, 2016). In the present study, we focused on the TMW to PMAW ratio, which is possibly the first trial in QTL mapping for carcass-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty eight chickens from two different experimental lines with pedigree control and multi-trait selection by Embrapa Swine and Poultry National Research Center (Brazil) were sequenced: 14 individuals from a paternal broiler line called TT (7 females and 7 males), and 14 from a layer line called CC (7 females and 7 males). Previously, these two experimental lines were used to generate a reciprocal F 2 Resource population for QTL mapping studies [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, Embrapa Swine and Poultry National Research Center maintains several chicken lines under multi-trait selection in Brazilian climatic and nutritional conditions for more than 20 years. Two of those lines, a white-egg type (layer) and a meat-type (broiler), due to considerable difference in their growth rates and carcass yields, were utilized to generate an F2 experimental population for QTL mapping studies [ 13 , 14 ]. The CC layer line used in this study is a white-egg laying hen originated from the White Leghorn, and it has been selected since 1989 mainly for reproductive traits such as egg production and fertility, besides egg quality traits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%